Promotion of Highly-Technological Products of Civil and Double Purpose of the Defense and Industrial Complex of Russia: Challenges, Efficiency and Prospects - S. A. Shvetsov; T. N. Yegorushkina; M. P. Kalinichenko (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
The article describes characteristics, problems and experience of promoting highly-technological products of civil and double purpose at entities (including enterprises) of the defense and industrial complex of Russia and provides recommendations aimed at increasing efficiency of this trend. The authors identify specific features of promoting highly-technological products of civil and double purpose, analyze key tools of marketing communications used in promotion with due regard to specificities of the target market and products. Promotion strategy for civil products of ‘Tulmashzavod’ was worked out and its efficiency was estimated. By analyzing the empiric material the authors put forward the trends whose development could foster improvement of economic and communication efficiency of promoting highly-technological products of civil and double purpose at home enterprises of the defense and industrial complex.